Metabolic effects of fasting on human and mouse blood in vivo. Issue 3 (4th March 2017) - Pietrocola, Federico; Demont, Yohann; Castoldi, Francesca; Enot, David; Durand, Sylvère; Semeraro, Michaela; Baracco, Elisa Elena; Pol, Jonathan; Bravo-San Pedro, Jose Manuel; Bordenave, Chloé; Levesque, Sarah; Humeau, Juliette; et al.
ABSTRACT: Starvation is a strong physiological stimulus of macroautophagy/autophagy. In this study, we addressed the question as to whether it would be possible to measure autophagy in blood cells after nutrient deprivation. Fasting of mice for 48 h (which causes ∼20% weight loss) or starvation of human volunteers for up to 4 d (which causes <2% weight loss) provokes major changes in the plasma metabolome, yet induces only relatively minor alterations in the intracellular metabolome of circulating leukocytes. White blood cells from mice and human volunteers responded to fasting with a marked reduction in protein lysine acetylation, affecting both nuclear and cytoplasmic compartments. In circulating leukocytes from mice that underwent 48-h fasting, an increase in LC3B lipidation (as assessed by immunoblotting and immunofluorescence) only became detectable if the protease inhibitor leupeptin was injected 2 h before drawing blood. Consistently, measurement of an enhanced autophagic flux was only possible if white blood cells from starved human volunteers were cultured in the presence or absence of leupeptin. Whereas all murine leukocyte subpopulations significantly increased the number of LC3B + puncta per cell in response to nutrient deprivation, only neutrophils from starved volunteers showed signs of activated autophagy (as determined by a combination of multi-color immunofluorescence, cytofluorometry and image analysis). Altogether, these results suggest that white blood cells are suitable for monitoring autophagic flux. In addition, we propose that the evaluation of protein acetylation in circulating leukocytes can be adopted as a biochemical marker of organismal energetic status.